2023
DOI: 10.1038/s41598-022-25908-6
|View full text |Cite
|
Sign up to set email alerts
|

Reinfection rate in a cohort of healthcare workers over 2 years of the COVID-19 pandemic

Abstract: In this large cohort of healthcare workers, we aimed to estimate the rate of reinfections by SARS-CoV-2 over 2 years of the COVID-19 pandemic. We investigated the proportion of reinfections among all the cases of SARS-CoV-2 infection from March 10, 2020 until March 10, 2022. Reinfection was defined as the appearance of new symptoms that on medical evaluation were suggestive of COVID-19 and confirmed by a positive RT-PCR. Symptoms had to occur more than 90 days after the previous infection. These 2 years were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
56
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 13 publications
2
56
0
Order By: Relevance
“…At present, studies on the reinfection rate of different SARS-CoV-2 VOCs are limited, and the results of previous studies are not completely consistent. A cohort study from Brazil showed that the SARS-CoV-2 reinfection rate in health workers was 4.3% during the Omicron period, which was higher than the period before Omicron (0.8%) [ 36 ]. A meta-analysis including 91 studies showed that the pooled rate of reinfection was highest in the Omicron-predominant period (3.31%), followed by the Delta- (1.25%) and Alpha- (0.57%) predominant periods [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies on the reinfection rate of different SARS-CoV-2 VOCs are limited, and the results of previous studies are not completely consistent. A cohort study from Brazil showed that the SARS-CoV-2 reinfection rate in health workers was 4.3% during the Omicron period, which was higher than the period before Omicron (0.8%) [ 36 ]. A meta-analysis including 91 studies showed that the pooled rate of reinfection was highest in the Omicron-predominant period (3.31%), followed by the Delta- (1.25%) and Alpha- (0.57%) predominant periods [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fourth year of the COVID-19 pandemic, the high numbers of circulating SARS-CoV-2 variants [1-3] and re-infected persons [4][5][6], the lack of decreasing trends in the global numbers of new daily cases [7,8], and the expected very long duration of the Omicron wave [9] make us think about the constant circulation of the pathogen, that is, about the endemic stage of the disease. To illustrate the global trends, let us use the accumulated numbers of laboratory-confirmed COVID-19 cases V j and deaths D j , the percentages of fully vaccinated people VC j and boosters BC j, and the results of calculation of the effective reproduction number R j [10].…”
Section: Introductionmentioning
confidence: 99%
“…Since a recent study reported that most cases of reinfection occurred during the Omicron period, the very low proportion could be accounted for by the follow-up period ending on December 31, 2021, which was the beginning of the Omicron period. 32 Seventh, due to the limitations of an observational study, reverse causality could not be fully solved with MVPA and COVID-19 outcomes.…”
Section: Discussionmentioning
confidence: 99%